Metodyka pracy szkolnych kół krajoznawczych w Polsce okresu międzywojennego - Magiera, Elżbieta (Biuletyn Historii Wychowania, 2018)
The article concerns work at school sightseeing clubs in Poland in the Interwar period. Since 1919, first in Krakow and then throughout Poland, school sightseeing clubs would emerge, especially in secondary schools and higher grades of elementary schools. Educational authorities supported the school sightseeing movement. The article shows an outline of the ideology of school sightseeing clubs, the stages of their internal development, the scope of activity and the assessment of their work carried out by the organizers. In Interwar Poland, the school sightseeing movement was a part of the innovative educational and didactic activities in schools.